Penjadwalan Pembelajaran Narapidana: Penerapan Algoritma Genetika di LPKA Kelas I Tanjung Gusta Medan - Yun Betry Siagian; Heri Santoso; Muhammad Dedi Irawan (Journal of Information Technology, 2024)
Scheduling in education has been a common issue faced, particularly concerning the mismatch between class hours and teacher availability. Addressing this necessitated careful precision and a significant amount of time for subject scheduling. Genetic algorithms emerged as a suitable choice for managing school subject scheduling due to their capability to address multi-criteria and multi-objective problems inspired by biological evolution. The concept of genetic algorithms could be effectively applied in the context of schedule arrangement within educational institutions. This study employed a quantitative methodology and implemented the Rapid Application Development (RAD) system development method. The utilization of genetic algorithms in subject scheduling, as demonstrated in this research, was deemed beneficial for correctional institutions previously engaged in manual scheduling processes. The outcomes indicated the success of the genetic algorithm approach in resolving school scheduling issues by seeking optimal scheduling combinations, as evidenced by achieving maximum fitness values and minimal errors (in this case, an error value of 0), indicating the absence of class schedule conflicts.